The growing importance of high-efficiency ultrasound in diagnosis and management of dermatological diseases - Trąbka, Natalia; Kowalczyk, Klaudia; Demidowicz, Gabriela; Lasota, Nina; Cichoń, Katarzyna; Chyćko, Małgorzata; Czarnota, Julia; Wiśniewski, Wojciech; Lambach, Maciej; Younes, Martyna (Journal of Education, Health and Sport, 2023)
Introduction: High-frequency ultrasonography (HF-USG) uses frequency above 20 MHz, which allows to visualize skin layers and measure their thickness. As it is simple, non-invasive and reliable technique, it has become a relevant tool in the field of dermatology along with other methods like for example dermoscopy. It can be used not only for the evaluation, diagnosis and management of various skin diseases, but also for analysis of the healthy skin structure Aim of the study: The aim of this review is to present information on the use of high-efficiency USG and its application in dermatology. Materials and methods: The literature available in the PubMed and Google Scholar data bases was reviewed, using the following keywords: "dermatologic ultrasound", "skin ultrasound, "HFUS dermatology". Conclusions: HFUS has given many opportunities in dermatology. Although ultrasound is not a new thing and it has been used in the field of dermatology for more than four decades, its significance has evolved with improvements in technology. We already have some pathognomonic sonographic features for skin lesions, but this amount will definitely increase due to the growing popularity of HFUS devices in clinical practice.